Complete works - Spinoza, Benedictus de 1632-1677; Morgan, Michael L.; Shirley Samuel (Indianapolis Hackett Publishing company, 2002)
The only single edition of the Spinoza corpus available in English, this volume features Samuel Shirley's pre-eminent translations of Ethics; Theological-Political Treatise; Treatise on the Emendation of the Intellect; Metaphysical Thoughts; The Letters; Principles of Cartesian Philosophy; and Political Treatise. Also includes The Short Treatise on God, Man, and His Well-Being, and Hebrew Grammar. Michael Morgan provides a general Introduction that places Spinoza in Western philosophy and culture, and sketches the philosophical, scientific, and religious moral and political dimensions of Spinoza's thought. Brief introductions to each work give succinct historical and philosophical overviews. A bibliography and index are also included.